MODEL PERTANIAN BIOINDUSTRI BERBASIS INTEGRASI SAWIT-SAPI DI PROVINSI RIAU - Dahono Dahono; Ida Nuristina; Oni Ekalinda; Agussalim Agussalim; Taufik Hidayat (UIR Press, 2019)
ABSTRACT The palm bioindustry farming model in Riau Province aims to utilize all factors of production. It can be turned into other products that are managed into bioenergy, as well as free of waste by applying the principles of reducing, reusing, and recycling (reduce, reuse and recycle). The agriculture-bioindustry model is expected to produce a healthy, sustainable environment, and can increase the income of palm farmers in the study area and increase the efficiency of oil palm farming. The bio-industrial agriculture model activity was carried out in Tapung District, Kampar Regency, Riau Province. It was started from January 2018 until December 2018. The scope of activities is in the form of coordination with related agencies, collecting primary data, introducing technology with socialization events and seeing the performance of bioindustry activities. The results of the activity can be reported that Tapung sub-district has a land area of 739.21 km2 or 73.921 ha, and an oil palm area of 34,102 ha, annual midrib production of 748,000 midribs (1,645,600 kg/year) with an average livestock feed needs 20 kg/day. It means that the Tapung sub-district can accommodate 228 animals in a year, out of 228 animals produce 1,140 kg of dry manure and produce 684 liters of urine per day, depending on the age and body-weight of the livestock. However, all the byproducts from cattle the oil palm is still being used for their own business needs and not yet for commercial use. Their own needs are in the form of impacts on farmers' palm production from the activities. It can be concluded that the performance of the bio-industry produces in higher palm oil production compared to existing ones.